EVALUATION OF TAX COLLECTION ON VERIFICATION SERVICES BY CRYPTOASSET VALIDATORS - Jatmika, Aqmarina Ishmah; Sari, Dahlia (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
The rise of cryptocurrencies has reshaped the global financial system, posing challenges in taxing crypto transactions and emphasizing the need for a unified and responsive regulatory framework. In response, Indonesia enacted PMK 68/2022 to regulate the taxation of crypto transactions. This qualitative research aims to evaluates the collection of Final Income Tax Article 22 on verification services by crypto-asset validators, based on “The Four Maxims” tax collection principle. Data were collected using in-depth interview with seven respondents, comprising four crypto-asset validators, two tax consultants, and one tax authorities as a form of triangulation. This study found that Article 22 Final Income Tax collection in Indonesia has met the convenience and efficiency principle of “The Four Maxims”. However, it failed to meet the criterion of certainty, owing to uncertainties in the definition and the method for calculating the tax basis. Also, the principle of equality is not realized due to the policy's focus on ease of administration and simplicity. The findings from this research are anticipated to assist tax authorities in formulating policies to enhance compliance among validators.